Effects of heat stress on growth metrics, carcass characteristics, telomere length, and gene expression in chickens - Musa, Aliyu Abduljalal; Mamat-Hamidi, Kamalludin; Idrus, Zulkifli; Chung, Eric Lim Teik; Samat, Noraini; Abu Kassim, Nafeesa (Elsevier Inc., 2025)
This study investigated the impact of heat stress (HS) on growth performance, carcass traits, telomere length (TL), and gene expression profiles in three chicken breeds with varying growth rates: slow-growing (SAGA), medium-growing (Sasso), and fast-growing (Cobb 500). Three hundred 14-day-old male chicks were exposed to either control (25°C) or HS (34°C for 6 hours/day) conditions for four weeks in a controlled environment. Weekly growth metrics, TL at two and four weeks, Heat Shock Protein 70 (HSP70) and Insulin-Like Growth Factor-1 (IGF-1) expression in muscle and liver at two and four weeks of HS exposure, and carcass/organ yields at four weeks were analyzed. Cobb 500 chickens exhibited significant growth reductions under HS, while SAGA showed resilience. Notably, SAGA chickens exhibited a significant increase in intestinal organ mass under HS, which may indicate an adaptive response to thermal stress. HS exposure significantly shortened TL across all breeds, suggesting its utility as a universal biomarker for HS in chickens. All breeds upregulated HSP70 expression, with the Cobb 500 showing the most prominent increase. Similarly, IGF-1 was expressed (upregulated), particularly in 500 broilers at both time-points, highlighting breed-specific differences in growth performance. These results demonstrate breed-specific physiological adaptations to HS. TL and stress-related gene expression are crucial indicators of heat susceptibility and adaptation. The study provides insights into developing breed-specific management and breeding strategies to enhance poultry resilience to increasing global temperatures.